Perbandingan Kemampuan Komunikasi Matematis Antara Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) dengan Think-Pair-Share (TPS) Pada Materi bilangan Bulat Bagi Siswa Kelas VII SMP IT Khairul Imam Medan - Nurin Natiqoh Lubis (EDUTECH, 2023)
This study aims to see that students' mathematical communication ability using cooperative learning model type Numbered Head Together (NHT) is better than cooperative learning model type Think Pair Share (TPS) on the matter of integers in class VII SMP IT Khairul Imam Medan.This type of research is a quasi experiment. The population in this study is all students of class VII Semester I SMP IT Khairul Imam Medan consisting of 8 classes with total students 272 people. Sampling was done by simple random sampling by taking 2 classes from 8 classes at random that is experiment class A that is class VII-3 which amounted to 35 people and experiment class B that is class VII-1 which amounted to 34 people. This research use one type instrumen is post-test only use to detemine the ability of mathematical communications that have been validated in the form of a description. The result of this research shows that with the difference of post-test data from experimental class A with cooperative learning model type NHT and experiment B class with cooperative learning model type TPS obtained average value of experiment class A is 77,23 and experiment class average value B by 70,86. The result of right side t test with dk = 67 and a = 0,05, obtained thitung = 1,8 and ttable = 1,669 so thitung ttable that is 1,8 1,669 Ha accepted, thus obtained by conclusion that mathematical communication ability use cooperative learning model type NHT higher of the cooperative learning model type TPS on the matter of integers in class VII SMP IT Khairul Imam Medan.